The Effect of Dividend Payout Ratio, Debt to Equity Ratio, and Return on Equity on Price Book Value in Telecommunications Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period - Shelvyana Novita Sari; Wahyudiono (NAROTAMA UNIVERSITY, Indonesia, 2023)
This study aims to analyze and empirically prove the effect of Dividend Payout Ratio, Debt to Equity Ratio, and Return on Equity on Price Book Value in Telecommunication Industry Sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period both partially and simultaneously. The approach used in this study is an associative approach. The population in the study was 22 companies and the sample used was 6 companies for five years using the purposive sampling method. Data analysis techniques use Classical Assumption Test, Multiple Linear Regression, Hypothesis Test (t Test and F Test) and Coefficient of Determination. The data processing program in the study used SPSS software version 26. The results of the study proved that partially the Dividend Payout Ratio and Return on Equity have a significant effect on the Price Book Value. Meanwhile, the Debt to Equity Ratio does not have a significant effect on the Price Book Value. Simultaneously, the Dividend Payout Ratio, Debt to Equity Ratio, and Return on Equity have a significant effect on the Price Book Value of Telecommunications Industry Sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period.